Tualang honey spray versus film spray (Opsite®) as post-long bone fracture fixation wound dressing: a comparative study - Sharifudin, Mohd Ariff; Shafei, Surianty; Ab Rahman, Shafuzain; Sadagatullah, Abdul Nawfar (2014)
Background of Study: Honey-based dressings have a potential benefit in treating wounds in implant-related surgery due to its anti-microbial activities and healing potentials. The study aims to compare Tualang honey spray with film spray (Opsite®) as an alternative dressing material following long bone fracture fixations. This is a preliminary study in Malaysia on human subjects. Materials and Methods: This is a randomized, controlled trial involving trauma patients with closed fracture diaphysis of tibia or femur internally stabilized with either plates or intramedullary devices. Forty patients were randomly divided into three groups according to the dressing material used; film spray (Opsite®) dressing (n=16), Tualang honey spray (n=13), and control group (n=11). Each group used a same wound protocol except for the control group in which involve application of non-adhesive film (Mepore) only. Dressing materials were applied immediately following surgery and on day three post-surgery after wound inspection. Assessment of wound performed on day 14 and day 42 post-surgery. Outcomes measured include wound complications, and the effects on skin commensals. On day 42, infection rate and scar formation were also evaluated. Results: A patient from the Opsite® spray group had surgical site infection. Acinobacter was isolated from one of the patients under the control group. There was no statistically significant association between wound healing and dressing methods used. All wounds healed without any evidence of infection at the end of the study. Tualang honey spray have a significant influence in reducing the risk of hypertrophic scar formation. Wound outcomes were also similar compared to Opsite® spray. Conclusion: Tualang honey spray is a safe alternative for wound dressing material comparable to the widely used Opsite* spray. It promotes good wound healing with a low risk of hypertrophic scar formation.